Characteristics of polyamide covers for sausage production - Strashynskyi, Igor; Pasichnyi, Vasyl; Omelchenok, Igor (My University, 2020)
The use of artificial materials as packaging provides ample opportunity to increase sausage production volumes but sets several additional requirements for the casings: invariability of diameter along the entire length; high elasticity; moisture resistance; ease of preparation for filling with minced meat; the possibility of automating the process of forming a product; the ability to preserve the markings applied. The casings are classified into several distinctive features. The most common division is by type of material. There are two large groups: natural (from the gastrointestinal tract of pets) and artificially created, which are divided into: casings made of natural raw materials (collagen, cellulose, fibrous) and synthetic (polymer films). Використання штучних матеріалів в якості упаковки надає широкі можливості для збільшення обсягів виробництва ковбасних виробів, але встановлює кілька додаткових вимог до оболонок: незмінність діаметра по всій довжині; висока еластичність; вологостійкість; простота підготовки до наповнення фаршем; можливість автоматизації процесу формування виробу; можливість збереження нанесеного маркування. Плівки класифікуються за кількома відмінними ознаками. Найпоширеніший поділ - за типом матеріалу. Існує дві великі групи: природні (із шлунково-кишкового тракту домашніх тварин) та штучно створені, які поділяються на: оболонки з натуральної сировини (колаген, целюлоза, волокнисті) та синтетичні (полімерні плівки).
Keywords: sausage casings; polyamide; sausage; ковбасні оболонки; поліамід; ковбасні вироби; кафедра технології м’яса і м’ясних продуктів